The Right to Belong: Individual Motives and Youth Gang Initiation Rites. Issue 11 (1st November 2016) - Descormiers, Karine; Corrado, Raymond R.
ABSTRACT: The current study uses a mixed-methods approach to describe the nature and context of the initiations undergone by 54 participants among a sample of 73 incarcerated gang members. The study describes and compares types of initiation and how they vary based on individual characteristics of the individuals being initiated. Three general types of initiation are found: (1) the ego violent event, (2) the crime commission, and (3) the expressive violence toward others. An ego violent initiation was more frequent among younger prospective members and those who were coerced into joining. Individuals who were looking for respect were more likely to be required to perpetrate an act of violence toward someone in order to get in. No individual characteristics were associated with crime commission type. The policy implications of such findings are discussed in conclusion.